Matrices of unitary moments - Dykema, Ken; Juschenko, Kate (MATHEMATICA SCANDINAVICA, 2011)
We investigate certain matrices composed of mixed, second-order moments of unitaries. The unitaries are taken from $C^*$-algebras with moments taken with respect to traces, or, alternatively, from matrix algebras with the usual trace. These sets are of interest in light of a theorem of E. Kirchberg about Connes' embedding problem.